Integration PBL with RMS: Improving problem solving skills on environmental education - Ahmad Muhlisin; S Siswanto; Suwito Singgih; Nuryunita Dewantari; Lilia Ellany Mohtar (Biosfer: Jurnal Pendidikan Biologi, 2020)
The environmental education course currently does not integrate problem-solving problem skills. The purpose of this study was analyzing the results of applying integration on problem-based learning with the RMS (reading, mind mapping, and sharing) learning model. The research method was a quasi-experimental with pre-test-post-test control group design. The study was conducted on 56 students who took an environmental education course in Natural Science Education Universitas Tidar. Data analysis used an Anacova test with a pretest as its covariate. The study results stated that 1) developed learning model integrates PBL with RMS learning model consisting of identifying problems, finding relevant information about problems through reading activities, analyzing problem: group discussion through mind mapping, providing solutions, and sharing results of mind mapping. 2) The integration of PBL with the RMS learning model indicated by an average score of post-test in the integration of PBL with the RMS learning model class of 68.46, and the traditional class of 48.92. 3) the learning process that occurs in the integration of PBL with the RMS learning model class shows that learning is run well, which is indicated by students' average evaluation score of the lecturer learning process. The integration of PBL and RMS model can be utilized by teachers and lecturers in Biology learning to have thinking skills and solve daily problems.